The Relationship of National, School, and Student Socioeconomic Status With Academic Achievement: A Model for Programme for International Student Assessment Reading and Mathematics Scores - Finch, Holmes; Finch, Maria E. Hernández (Frontiers in Education, 2022)
Prior research has demonstrated links between academic achievement and family socioeconomic status SES, such that students from wealthier families generally exhibit higher academic performance. Recent work has also shown that students who attend schools with greater SES inequality and lower average family income also tend to have lower achievement test scores. Additional research has found that students from poorer nations have lower average achievement test scores. Despite the presence of this evidence supporting individual relationships between SES and achievement test performance, there is less extant information positing a mechanism for how these relationships at different levels interact with one another and are related to achievement test performance. The purpose of the current study was to propose and test two multilevel mediation models of the relationships between national funding for public services such as education, and economic inequality with shortages for educational resources and trained staff, as well as aggregated and individual family SES with academic achievement. Results demonstrated that a partially mediated model yielded good fit to the data with both direct and indirect relationships among national funding for public services and academic achievement, as mediated through school level resource shortages and family SES. Implications of these results are discussed.